Tantangan Teknologi Metaverse dan Avatar pada Lembaga Pendidikan Islam - Zuhri Fahruddin; Mochammad Marjuki; Elok Aini Sulthon (Fahima, 2026)
This study aims to examine the impact of Artificial Intelligence (AI) technology on Islamic educational institutions. This study uses descriptive qualitative with library research to find various reference sources related to the research object. In the form of books, journals and research results. The use of Artificial Intelligence (AI) technology blindly in Islamic educational institutions will cause dehumanization, meaning that the role and function of Islamic Education teachers are eroded, with the presence of Cyborgs and avatars (virtual sensations and engineering reality) there are no more teachers interacting physically but only with virtual and engineering reality, there are no physical teachers, students, and physical institutions.